Welcome :: Homework Help and Answers :: Mathskey.com
Welcome to Mathskey.com Question & Answers Community. Ask any math/science homework question and receive answers from other members of the community.

13,401 questions

17,804 answers

1,438 comments

43,518 users

Find the equationof the tangent and the normal to the curve y=2x^3-x+5 at the point (1,6)?

0 votes

full working out please ^__^

asked Feb 27, 2014 in CALCULUS by homeworkhelp Mentor

2 Answers

0 votes

Point slope form is y-y1 = m(x-x1)

Add y1 to each side.

y = m(x-x1)+y1 ---> (1)

Where m is slope, (x1,y1) = (1,6) are point on the line.

Now find f'(x) 

f(1) = 2-1+5 = 6

f(6) = 432-6+5 = 431

f'(x) = f(b)-f(a)/b-a

= (431-6)/(6-1)

= 425/5

= 85

For a line tangent to a curve

Slope m = f'(x), (x1,y1) = (1,6)

From (1)

y = 85(x-1)+6

y = 85x-85+6

y = 85x-79

For a line normal to a curve is

Slope is m = -1/f'(a) , (x1,y1) = (1,6)

From (1)

y = -1/85 (x-1)+6

y = -x/85+1/85+6

y = -x/85 +511/85

y = -x/85+6.01

answered Feb 27, 2014 by ashokavf Scholar

The tangent line equation to the curve y =  2x3 - x + 5 at the point (1, 6).is y = 5x + 1.

The normal line equation to the curve y =  2x3 - x + 5 at the point (1, 6) is y = (- 1/5)x + (31/5).

0 votes

The curve y =  2x3 - x + 5 and the point is (1, 6).

y ' = 6x2 - 1.

When, x = 1, y ' = 6(1)2 - 1 = 6 - 1 = 5.

y ' = 5.

This is the slope (m ) of the tangent line to the implicit curve at (1, 6).

 

Slope - intercept form line equation is y = mx + b, where m is slope and b is y - intercept.

Now the tangent line equation is y = 5x  + b.

Find the y - intercept by substituting the the point in the tangent line equation say (x, y) = (1, 6).

6 = 5(1) + b

b = 6 - 5

⇒ b = 1.

The tangent line equation  is y = 5x + 1.

 

The normal line and tangent are perpendecular to each other.

Since the slopes of perpendecular lines are negative reciprocals the slope of nolmal line through the point  (1, 6) is - 1/5.

Slope (m) = - 1/5.

Now, the normal line equation is y = (- 1/5)x + b.

Find the y - intercept by substituting the the point in the normal line equation say (x, y) = (1, 6).

6 = (- 1/5)(1) + b

b = 6 + 1/5

b = (30 + 1)/5

b = 31/5.

The normal line equation  is y = (- 1/5)x + (31/5).

answered Jun 18, 2014 by lilly Expert

Related questions

...